Development of Swimming Learning Models Through Adobe Flash Application Media in High Schools - Zulkifli, Zulkifli; Henjilito, Raffly; Yani, Ahmad; Alficandra, Alficandra; Makorohim, M Fransazeli; Yudho, Pijar Kuncoro; Zhuo, Pua Ying (Faculty of Sport and Health Sciences, 2023)
This study aims to produce a product in the form of a CS 6 Flash-Based Swimming Learning Model so that students can more easily understand swimming material and also make it easier for teachers to teach swimming. This study uses the Research and Development method. The steps in this research were: field needs analysis, compiling products, validating media and material experts, small-scale trials, second stage validation, large-scale trials, and the final product. The subjects of this study were students of class XI SMA Islam Az-Zahrah Palembang. Data was collected using a questionnaire for both experts and subjects. The results of this study are in the form of swimming learning models for teachers. Material experts state that this product is included in the good category (84.6%). Application experts stated that this product was included in the good/proper category with a percentage of 90.62% while for the small group and field assessment were 87.5% and 90.90%, respectively. It can be concluded that the development of this application can be used as a reference for teachers in the process of learning swimming material and the findings in this study are the results of applying swimming material to high school students from class XI.